Transhepatic embolization of a congenital intrahepatic portosystemic shunt for the treatment of hepatic encephalopathy in a noncirrhotic patient using Amplatzer vascular plug device - Rachel Ann Brader, BS; Kyung Rae Kim, MD (Radiology Case Reports, 2017)
A 73-year-old male with no history of liver disease was hospitalized for weakness, confusion, ataxia, and new onset hepatic encephalopathy with hyperammonemia. After management with lactulose and rifaximin, his symptoms persisted, and he underwent transjugular liver biopsy. Biopsy showed normal liver, but a portosystemic shunt was incidentally identified on postbiopsy venogram. The patient underwent occlusion of the shunt with two Amplatzer vascular plugs and four Nester coils. Following embolization, the patient’s symptoms resolved completely. Our case reports one of the oldest adults to present with symptoms from a congenital portosystemic shunt. Congenital portosystemic shunts can be considered in patients with new onset hepatic encephalopathy in the absence of underlying liver disease. Prognosis after embolization of congenital portosystemic shunt is great, and embolization may result in full reversal of symptoms.